Diversity of Cryptosporidium spp. in Apodemus spp. in Europe - Čondlová, Šárka; Horčičková, Michaela; Havrdová, Nikola; Sak, Bohumil; Hlásková, Lenka; Perec-Matysiak, Agnieszka; Kicia, Marta; McEvoy, John; Kváč, Martin (European journal of protistology, 2019)
The genetic diversity of Cryptosporidium spp. in Apodemus spp. (striped field mouse, yellow-necked mouse and wood mouse) from 16 European countries was examined by PCR/sequencing of isolates from 437 animals. Overall, 13.7% (60/437) of animals were positive for Cryptosporidium by PCR. Phylogenetic analysis of small-subunit rRNA, Cryptosporidium oocyst wall protein and actin gene sequences showed the presence of Cryptosporidium ditrichi (22/60), Cryptosporidium apodemi (13/60), Cryptosporidium apodemus genotype I (8/60), Cryptosporidium apodemus genotype II (9/60), Cryptosporidium parvum (2/60), Cryptosporidium microti (2/60), Cryptosporidium muris (2/60) and Cryptosporidium tyzzeri (2/60). At the gp60 locus, novel gp60 families XVIIa and XVIIIa were identified in Cryptosporidium apodemus genotype I and II, respectively, subtype IIaA16G1R1b was identified in C. parvum, and subtypes IXaA8 and IXcA6 in C. tyzzeri. Only animals infected with C. ditrichi, C. apodemi, and Cryptosporidium apodemus genotypes shed oocysts that were detectable by microscopy, with the infection intensity ranging from 2000 to 52,000 oocysts per gram of faeces. None of the faecal samples was diarrheic in the time of the sampling.
Keywords: Cryptosporidiosis; RNA ribozomální 18S; Genetic Variation; Evropa; myši; zvířata; genotyp; Europe; genetická variace; RNA, Ribosomal, 18S; Mice; Animals; Murinae; kryptosporidióza; Cryptosporidium; Genotype